GAMBARAN ARUS PUNCAK EKSPIRASI PADA PETANI JERUK DI DESA PETANG - Suparwati, Komang Tri Adi; Paramurthi, I.A Pascha; Wahyuni Novianti, I Gst Ayu Sri; Astrawan, I Putu; Krismantara, I Ketut Arya Yoga (Prodi Fisioterapi UFDK, 2025)
ABSTRACTExposure to organophosphate pesticides will affect lung function which causes irritation, airway narrowing and decreased lung function. This condition is experienced by farmers through various activities such as the process of bringing pesticides to the farm, the process of mixing pesticides, the process of spraying pesticides on the farm and washing the tools that have been used to spray, all of these activities have the potential to cause exposure to farmers either through the skin or breathing. The symptoms of exposure to organophosphate pesticides such as shortness of breath and respiratory tract irritation resulting in a decrease in the value of peak expiratory flow (APE). The purpose of the study was to determine the value of Peak Expiratory Flow (APE) in citrus farmers in Petang Village. This study used descriptive analysis with a total of 30 respondents. The instrument in this study used a peak flow meter to measure the peak expiratory flow value of citrus farmers. The results of this study showed that the Peak Expiratory Flow value in the green zone was 6 respondents (20%), the yellow zone was 19 respondents (63.3%) and the red zone was 5 respondents (16.7%). Keywords: expiratory peak flow, citrus_farmer, pesticides ABSTRAKPaparan pestisida jenis organofosfat akan mempengaruhi fungsi paru yang dimana menimbulkan efek iritasi, penyempitan saluran nafas dan penurunan faal paru. Kondisi tersebut dialami oleh petani melalui berbagai kegiatan seperti proses membawa pestisida menuju lahan pertanian, proses pencampuran pestisida, proses penyemprotan pestisida di lahan pertanian dan mencuci alat yang sudah digunakan menyemprot, semua aktivitas ini berpotensi menimbulkan paparan pada petani baik melalui kulit ataupun pernapasan. Adapun gejala dari paparan pestisida jenis organofosfat seperti sesak nafas dan iritasi saluran pernapasan sehingga mengakibatkan penurunan nilai arus puncak ekspirasi (APE). Tujuan dari penelitian untuk mengetahui nilai Arus Puncak Ekspirasi (APE) pada petani jeruk di Desa Petang. Penelitian ini menggunakan analisis deskriptif dengan total 30 responden. Instrumen dalam penelitian ini menggunakan peak flow meter untuk mengukur nilai Arus Puncak Espirasi petani jeruk. Hasil dari penelitian ini menunjukkan bahwa nilai Arus Puncak Ekspirasi pada zona hijau adalah 6 responden (20%), zona kuning adalah 19 responden (63,3%) dan zona merah adalah 5 responden (16,7%). Kata kunci: arus_puncak_ekspirasi, petani_jeruk, pestisida